Medieval Interpretations of the Quran: A Historical Perspective - Fikri Fillaili (Senarai: Journal of Islamic Heritage and Civilization, 2024)
The medieval period in Islamic intellectual history represents a pivotal phase in the development of Qur'anic exegesis. Mufassirs, influenced by diverse scholarly backgrounds and ideological stances, introduced interpretations that reflected the intellectual and socio-cultural dynamics of their time. This study examines the various interpretive styles of the period, including linguistic, jurisprudential, philosophical, theological, mystical, and scientific approaches. These interpretations reveal that tafsir was not merely a theological discipline but also a response to political, social, and cultural realities. Key characteristics of this era’s tafsir include the imposition of personal ideas, ideological biases, repetition, and partiality, which challenge more holistic and comprehensive exegetical methods. Through this analysis, readers are invited to reconsider the role of mufassirs and their contributions to contemporary tafsir development